Prime minister tony blair's speech at the Annual Labour Party Conference 2003: an analysis of exigence and transitivity based on CDA and SFL - Martins, José Carlos (2007)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.